Brain-infiltrated monocyte macrophages in a rat model of temporal lobe epilepsy: revisiting the pro-inflammatory paradigm - Grabon, Wanda; Gasmi, Nadia; Lang, Anatole; Ruiz, Anne; Georges, Béatrice; Blot, Victor; Ogier, Michaël; Rheims, Sylvain; Navarro, Fabrice P; Bezin, Laurent (Frontiers in Immunology, 2025)
Neuroinflammation is central to temporal lobe epilepsy, yet the specific role of myeloid cells remains unclear. In status epilepticus (SE) models, circulating monocytes infiltrate the brain, although distinguishing them from microglia is challenging. Using a rat model, we traced infiltrating monocytes post-SE to investigate their persistence, phenotypic evolution during epileptogenesis and contribution to neuroinflammation. By tracking phagocytosed fluorescent nanoparticles and performing CD68 immunohistochemistry, we confirmed that monocytes entered the brain in significant numbers 24 hours post-SE, after the inflammatory peak occurred (7 hours). Their long-term presence and evolution into monocyte-macrophages (mo-mΦs) up to 7 weeks were monitored histologically using CD68. Distinct inflammatory profiles were further characterized after cell enrichment and fluorescence-activated cell sorting (FACS) distinguishing monocytes/mo-mΦs (CD11b+CD45hiCD11ahi) from microglia (CD11b+CD45loCD11alo). Microglia were the main drivers of the early pro-inflammatory response, with TNFα transcript levels nearly 14-fold higher in microglia than in monocytes 24h post-SE. In contrast, 24h post-SE, infiltrating monocytes transiently displayed an anti-inflammatory and neuroprotective phenotype, being the main source of IL-10, showing ~4-fold higher CD206, and expressing Arg1 absent in microglia. Tracked up to 7 weeks, these cells progressively adopted a microglia-like phenotype, contributed to the microglial scar and, although their expression of pro-inflammatory markers resembled nonactivated microglia, we hypothesize that their persistent presence might fuel the low-grade inflammation typical of chronic epilepsy. Importantly, since infiltrating monocytes initially engage in a transient anti-inflammatory response, strategies aiming to sustain or enhance this protective role in the context of epileptogenesis and epilepsy may open promising avenues for therapeutic intervention.